What Goes Up Must Come Down? Experimental Evidence on Intuitive Forecasting - Beshears, John; Choi, James J.; Fuster, Andreas; Laibson, David; Madrian, Brigitte C. (The American economic review, 2013)
Do laboratory subjects correctly perceive the dynamics of a mean-reverting time series? In our experiment, subjects receive historical data and make forecasts at different horizons. The time series process that we use features short-run momentum and long-run partial mean reversion. Half of the subjects see a version of this process in which the momentum and partial mean reversion unfold over ten periods (“fast”), while the other subjects see a version with dynamics that unfold over 50 periods (“slow”). Typical subjects recognize most of the mean reversion of the fast process and none of the mean reversion of the slow process.